Cryptococcus neoformans Infection Induces IL-17 Production by Promoting STAT3 Phosphorylation in CD4+ T Cells - Guo, Xiaoman; Mao, Xinru; Tian, Di; Liao, Yixin; Su, Bintao; Ye, Chaoliang; Shi, Dongling; Liu, Tie Fu; Ling, Yun; Hao, Yi (Frontiers in Immunology, 2022)
Cryptococcus neoformans infection in central nervous system is a severe infectious disease with poor outcomes and high mortality. It has been estimated 220,000 new cases each year. Over 90% of the cryptococcus neoformans meningitis were diagnosed in AIDS patients with CD4+ T cell count <100 cells/μL, however, the mechanism(s) of cryptococcal meningitis in patients with normal immune functions remains unclear. IL-17 is a pro-inflammatory cytokine and plays an important role in anti-fungal immunity. Here, we report that significant high levels of IL-17 were predominantly detected in cerebrospinal fluid of patients with either AIDS- or non-AIDS-associated cryptococcus neoformans meningitis but not in patients with tuberculous meningitis or non-neurosyphilis, antifungal therapy minimized IL-17 level in cerebrospinal fluid. In vitro mechanistic study showed that cryptococcus neoformans stimulation of healthy peripheral blood mononuclear cells prompted IL-17 production and CD4+ T cells were the predominant IL-17-producing cells. IL-17 production by cryptococcus neoformans stimulation was STAT3 signaling-dependent, inhibition of STAT3 phosphorylation attenuated cryptococcus neoformans-mediated IL-17 expression. Our data highlighted the significance of CD4+ T cells in antifungal immunity, and suggested IL-17 as a diagnostic biomarker of cryptococcus neoformans infection and STAT3 as a checkpoint for antifungal targeting therapies.